2000
DOI: 10.1007/s004499900154
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modeling and simulation of continuous airlift bioreactors

Abstract: For dynamic behaviors of continuous airlift bioreactors, a mathematical model based on a tanks-inseries model with back¯ow has been developed. The equations describing the dynamics of airlift bioreactors are material balances for micro-organism, substrate, dissolved oxygen and oxygen in gas-phase and heat balances. Nonideal mixing of liquid and gas phases is taken into account using a tanks-in-series model with back¯ow. The batch operation, startup operation and the consequence of plant failure were simulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…For larger Pe, the airlift system becomes closer to plug flow conditions and when Pe is smaller it indicates that the system is closer to being well-mixed. Within concentric tube airlift bioreactors, it is often assumed that the downcomer section is plug flow (Kanai et al, 2000;Znad et al, 2004), with the riser column being more well-mixed in nature. It should be noted that this study provides an overall Pe for the airlift vessel, which is commonly reported in studies comparing hydrodynamic parameters in systems under different conditions (Giovannettone and Gulliver, 2008;Merchuk et al, 1998).…”
Section: Oxygen Volumetric Mass Transfer Coefficientsmentioning
confidence: 99%
“…For larger Pe, the airlift system becomes closer to plug flow conditions and when Pe is smaller it indicates that the system is closer to being well-mixed. Within concentric tube airlift bioreactors, it is often assumed that the downcomer section is plug flow (Kanai et al, 2000;Znad et al, 2004), with the riser column being more well-mixed in nature. It should be noted that this study provides an overall Pe for the airlift vessel, which is commonly reported in studies comparing hydrodynamic parameters in systems under different conditions (Giovannettone and Gulliver, 2008;Merchuk et al, 1998).…”
Section: Oxygen Volumetric Mass Transfer Coefficientsmentioning
confidence: 99%
“…5. The fiber-side pressure change can be written as: P r,j = P r,j−1 + P j (16) where Fig. 7 illustrates dynamic performance of methane recovery with the operating and feed conditions given in Table 4.…”
Section: Dynamic Simulation Of Two-stage Membrane Separation With Recmentioning
confidence: 99%
“…An understanding of dynamic performance of gas membrane separation processes is essential for rational design and operation of industrial scale gas separation membrane modules. A dynamic model taking account of nonideal mixing can provide practical information for startup and shutdown operations, the transition between two stationary states, optimal design and operability studies besides a steady-state performance [16,17]. To the best of our knowledge, on the basis of the tanks-in-series concept the unsteady-state phenomena of the membrane separation have not yet been modeled in the open literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is known that the downcomer section in airlift systems is nearly plug flow relative to the riser, and has been represented as 10 tanks-in-series by other authors in studies of airlifts of similar size to that used in the current study. 9,11 It has been stated that the number of tanks in series does not have a strong effect on simulation results, 10 and therefore, the number of tanksin-series used to represent all flow rates was selected to be 11. These 11 well-mixed tanks were distributed as shown in Fig.…”
Section: Airlift Conceptualizationmentioning
confidence: 99%